Carbon Accounting from a Modern Accounting Perspective: Challenges and Implementation - Deny Purwo Sambodo (Nomico, 2026)
Carbon accounting has emerged as a critical dimension of modern accounting practice, yet its integration into mainstream financial reporting remains fragmented and contested. This article examines carbon accounting through the lens of contemporary accounting theory, exploring the conceptual foundations, key challenges, and practical implementation strategies encountered by organisations across diverse regulatory and economic contexts. Employing a systematic literature review methodology, this study synthesises evidence from 25 peer-reviewed studies published between 2021 and 2026 to identify prevailing trends, persistent gaps, and strategic opportunities in the field. The findings reveal that while the Greenhouse Gas (GHG) Protocol and emerging frameworks such as the International Sustainability Standards Board (ISSB) IFRS S1/S2 have advanced standardisation efforts, significant challenges remain in boundary delineation, Scope 3 reporting completeness, technological readiness, and ethical compliance. Crucially, most organisations treat carbon accounting as a compliance exercise rather than a strategic management tool, limiting its potential to drive genuine decarbonisation. This article contributes a novel integrative framework that maps accounting challenges onto implementation strategies, offering actionable guidance for practitioners, standard-setters, and policymakers committed to embedding carbon accountability within the architecture of modern accounting.